Kewenangan Jaksa dalam Memulihkan Kekayaan Negara - Albatul, Fatimah (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2014)
Abstract: This article discusses about the authority of the prosecutor in restoring the states assets based on Undang-Undang Kejaksaan No. 16 tahun 2004. Such a constitusional authority is in the form of obtainning special authorization from the government agencies as defined in article 30 paragraph 2 of Undang-Undang Kejaksaan. The scope of the authority includes, law enforcement, legal aid, legal consideration, saving and restoring the states wealth. In accordance with restoring the states wealth, it can be done by filing a lawsuit in court or by offering peace outside of the court. The authority of prosecutor in restoring the states wealth, according to the political jurisprudence, is valid in accordance with the authority of hisbah as a government official supervisor to resolve the dispute in the case of administrative irregularities. So, the prosecutors attempt to resolve the dispute can be justified, either by the litigation or non-litigation way. Likewise, it is the hisbah which has the authority to do prosecution and call the parties to be peacefully resolved. Keywords: Prosecutor, recovery, wealth, state, political jurisprudence